Dynamics of natural regeneration in Pinus laricio stands from southern Apennines (Italy) - Albanesi E; Mercurio R; Gugliotta OI (Forest@, 2006)
The seedlings establishment was studied in small (380 m2), medium (855 m2) and large (1520 m2) gaps created in calabrian pine (Pinus laricio Poiret ) stands (mean height 22 m) in the Southern Apennine. After three growing seasons first results put in evidence: a) no significant differences of water soil content were observed between gap sizes; b) transmittance was higher in large and medium gaps than in small ones and in the centre and northern sides in both gap sizes; c) calabrian pine seedling density was higher in large gaps than in medium and small ones and namely in the centre positions; silver fir seedlings appear after the second growing season in small and medium gaps; d) seedling mortality of calabrian pine was relevant in small and medium gaps in the edge and silver fir seedling mortality in the centre of the large ones; e) in these first years the ground vegetation (bramble and bracken) represents a moderate detrimental effect on seedlings establishment that could be removed by partial cuttings.